FMS: A Computer Network Fault Management System Based on The OSI Standards - Jailani, Norleyza; Patel, Ahmed (Malaysian Journal of Computer Science, 1998)
Deals with the management of network faults using management applications based on the OSI standards. Presents the problem domain and a prototype system that provides several fault management applications.